Conservative and antirevolutionary ideology in the scarlet letter: a new historicist analysis - Ismaznizam Jesmaj Azyze (Penerbitan UKM, 2007)
This essay presents a New Historicist analysis of Hawthorne’s most acclaimed novel, The Scarlet Letter.1 The analysis focuses on the interplay between Hawthorne’s nineteenthcentury ideology and the novel’s seventeenth-century cultural setting. The inclusion of “The Custom House,” an authorial introduction to the novel, is treated as highly significant as it presents a form of historical and ideological juxtaposition of Hawthorne’s nineteenth-century ideology with the novel’s seventeenth-century cultural setting. Biographical narratives on Hawthorne and historical narratives on nineteenth-century America are used extensively in this analysis as they offer valuable insights into the fictional formation of The Scarlet Letter. By historically establishing Hawthorne’s conservative attitudes towards forms of revolutionary activities, this essay explicates how the structure, characterizations and themes of The Scarlet Letter are carefully formed to serve those very conservative attitudes